Pengaruh Penggunaan Media Visual dan Kartu Flash dalam Pembelajaran Bahasa terhadap Peningkatan Prestasi Siswa - Marry Damayanti; Subanji; Dasna, Wayan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Abstract This research originated from the problem of declining learning achievement of students of SD Negeri Sukun 3 Malang City One of the indicators of declining student learning achievement is the results of the odd 2023/2024 Mid-Semester Exam (UTS) which was carried out in September 2023. Of the 25 students who took part in UTS, KKM scores were obtained that did not meet the learning completeness. In the results of the 2023/2024 odd semester UTS held in September 2021, data was obtained that the average score of Grade VI students is still below the KKM score in English subjects. This study aims to determine the influence of flashcards and visual media in English learning on improving student achievement at SD Negeri Sukun 3, Malang City. The method used to analyze the data used logit regression with 25 active student respondents. Indicators to determine student learning achievement use a Likert scale of 1-4. The study Control class and experimental class results showed that the value of count = 3.74 and table = 1.685 where tcal> ttable so that H0 was rejected and Ha was accepted. This means that it can be concluded that the use of visual media can be used as a learning medium that can improve student achievement compared to flashcard media. This is because visual media has a high appeal and is colorful so it can support the learning process. Visual media makes the learning process It is easy to implement because it can increase the child's focus on the material presented. Keywords: flashcard, Visual Learning Media, increased student achievement